Self-Regulation as a Moderator Between Husband’s Support and Inter-Role Conflict in Student-Mothers: Academic Demands and Role Juggling - Iskandar, Desiree Rizkika; Suharso, Puji Lestari (LPPM Universitas Pendidikan Mandalika, 2025)
This study investigates the relationship between perceived social support from husbands and inter-role conflict among student-mothers, with self-regulation as a moderating variable. This study used a quantitative, non-experimental design with a cross-sectional online survey. Participants were 147 Indonesian student-mothers enrolled in master’s and doctoral programs, all of whom were married, had children, were not employed, and did not live with extended family members. Data were collected using three standardized instruments: the Social Provision Scale (SPS), the School-Family Conflict Scale (SKS), and the Self-Regulation Scale (SRD). Data were analyzed using descriptive statistics, Pearson correlation, and moderated regression with Hayes’ PROCESS macro. Results showed that higher husband support significantly reduced inter-role conflict. However, self-regulation did not moderate this relationship. The findings emphasize the importance of husbands’ involvement in supporting student-mothers pursuing higher education.